A new species of lithistid sponge hiding within the Isabella mirabilis species complex (Porifera: Demospongiae: Tetractinellida) from seamounts of the Norfolk Ridge - Ekins, Merrick; Erpenbeck, Dirk; Wörheide, Gert; Hooper, John N. A. (Zootaxa, 2016)
A population level study of the lithistid (‘rock’) sponge, Isabella mirabilis, revealed a new species, Isabella tanoa sp. nov., living on five seamounts on the Norfolk Ridge, SW Pacific, and representing the third species to be discovered since the genus was first described in 2005. Comparisons between the three species showed significant differences in morphological characters that corresponded to differences in their respective CO1 barcoding sequences. Conversely, three of the four genotypes of Isabella mirabilis remain unresolved using morphological markers.